Requisitos de Autocuidado y su Relación con el Pie Diabético en personas con Diabetes Mellitus-Trujillo 2015 - Infante Puelles, Ruth Esther (2015)
Research descriptive - correlational cross-sectional was conducted in people diagnosed with diabetes mellitus attending the Primary Care Center III Metropolitan -Essalud and Aprovida center in 2015, with the aim of determining the relationship between the compliance requirements and the degree of self-care in the diabetic foot. The sample consisted of 278 adults diagnosed with diabetes mellitus selected according to the inclusion criteria. Scale self-care requirements (ERA), and Rating Scale diabetic foot: To collect data two instruments were used. The results are: 67.6% does not meet the requirements of self care, 52.2% are in category I for grade 0 where standing is at risk without injury, 93.5% of people who are category III, are in grades IV and V and does not meet the requirements of self-care. The conclusion: There is a relationship between compliance requirements and the degree of self diabetic foot less to more fulfillment foot injuries. Keywords: Self-care requirements, Diabetes Mellitus, Diabetic Foot